ASUHAN KEPERAWATAN KELUARGA PADA NY,S DENGAN HIPERTENSI MELALUI PENERAPAN TERAPI PIJAT KAKIDI DESA KUALU NENAS - Mahdalena Rahmadani; Ridha Hidayat; Indrawati (Jurnal Spektrum Kesehatan Indonesia, 2025)
The increasing prevalence of elderly people has led to various changes that impact health problems, such as decreased heart function, one of which is hypertension. Hypertension is a circulatory system disorder that can cause blood pressure to rise above normal values, namely systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. Non-pharmacological therapy that can be provided to hypertension sufferers includes effluarge foot massage therapy combined with garlic oil. Based on observations of real-world conditions, it was found that hypertensive patients experienced acute pain. Treatment for acute pain includes effluarge foot massage therapy using garlic oil. The results of this study revealed that Mrs. S's pain assessment revealed P (high blood pressure), Q (stabbing and pressing), R (back of the head, neck, and nape), a pain scale of 4, T (recurring and intermittent), and BP of 170/100 mmHg. The nursing diagnosis for Mrs. S was acute pain related to increased blood pressure. The nursing intervention provided to Mrs. S was effluarge foot massage therapy using garlic oil to reduce pain in hypertensive patients. The nursing implementation was in accordance with the established interventions until the acute pain problem was resolved, and there were no significant differences compared to previous research. Nurses are expected to apply effluarge foot massage therapy using garlic oil to hypertensive patients to address acute pain.